Extracellular DNA NET-Works With Dire Consequences for Health. Issue 4 (2nd August 2019) - Sorvillo, Nicoletta; Cherpokova, Deya; Martinod, Kimberly; Wagner, Denisa D.
Abstract : Neutrophils play a central role in innate immune defense. Advances in neutrophil biology have brought to light the capacity of neutrophils to release their decondensed chromatin and form large extracellular DNA networks called neutrophil extracellular traps (NETs). NETs are produced in response to many infectious and noninfectious stimuli and, together with fibrin, block the invasion of pathogens. However, their formation in inflamed blood vessels produces a scaffold that supports thrombosis, generates neo-antigens favoring autoimmunity, and aggravates damage in ischemia/reperfusion injury. NET formation can also be induced by cancer and promotes tumor progression. Formation of NETs within organs can be immediately detrimental, such as in lung alveoli, where they affect respiration, or they can be harmful over longer periods of time. For example, NETs initiate excessive deposition of collagen, resulting in fibrosis, thus likely contributing to heart failure. Here, we summarize the latest knowledge on NET generation and discuss how excessive NET formation mediates propagation of thrombosis and inflammation and, thereby, contributes to various diseases. There are many ways in which NET formation could be averted or NETs neutralized to prevent their detrimental consequences, and we will provide an overview of these possibilities.